KEBIJAKAN SEKOLAH DALAM PENERAPAN KARAKTER DISIPLIN SISWA DI SDN 77 REJANG LEBONG - Septi Yani; Kusen Kusen; Ummul Khair (Institut PTIQ Jakarta, 2020)
This study aimed to find out a depiction of school policies in the implementation of students’ disciplinary character at SDN 77 of Rejang Lebong Regency, Bengkulu. This study used a qualitative approach, and the subjects were Islamic education teachers, classroom teachers, and the school principal. Subsequently, the data collection techniques of this study were observation, interviews, and documentation. Data analysis adopted Miles’ et al theory comprised of data reduction, data presentation, and drawing conclusion. This study concluded that the application of disciplinary character education was integrated into subjects in accordance with the materials and objectives to be achieved and resting upon the school culture including class culture. Class culture referred to the culture associated with the application of disciplinary character education and responsibility as seen from the activities commonly carried out in the classroom and outside the classroom.